Nitric oxide synthase inhibitors in cardiogenic shock: present and future. (March 2008) - Kaluski, Edo; Uriel, Nir; Milo-Cotter, Olga; Klapholz, Marc
Cardiogenic shock (CS) accompanying myocardial infarction carries a case fatality rate of 40––50%. Profound myocardial dysfunction is partially reversible, and possibly related to a state of inflammatory storm accompanied by nitric oxide (NO) overproduction. CS survivors enjoy satisfactory longevity and quality of life. The focus of this review is to describe the available data regarding NO synthase (NOS) inhibitors in CS. In view of supportive evidence from mammalian research (inducible-NOS-knockout mice are less susceptible to ischemic and reperfusion injury), therapies mitigating NO overproduction were tested in human CS subjects. Human randomized clinical trials project excellent safety but lack of efficacy. Although the Phase III, multicenter, prospective, randomized, double-blind, placebo-controlled Study to Assess the Safety and Efficacy of Tilarginine Acetate (L -N G -monomethyl arginine citrate [L -NMMA]) in CS (TRIUMPH) trial demonstrated lack of clinical benefit of 5-h infusion ofL -NMMA in CS, major design issues regarding the optimal timing, dosing, duration and NOS inhibitor need to be addressed prior to rendering this therapy ineffective.